2018
DOI: 10.1159/000489884
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Satiety Hormones in Response to Leptin Treatment in a Patient with Leptin Deficiency

Abstract: Background: We tested whether leptin treatment affects secretion of satiety-related gut peptides and brain-derived neurotrophic factor (BDNF), which is a regulator of energy homeostasis downstream of hypothalamic leptin signaling. Methods: We report the case of a morbidly obese 14.7-year-old girl with a novel previously reported homozygous leptin gene mutation, in whom hormone secretion was evaluated in 30-min intervals for 10 h (07.30–17.30) to assess BDNF, insulin, glucagon-like peptide-1 (GLP-1), ghrelin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Treatment with recombinant human leptin (r-metHuLeptin; metreleptin) of patients with CLD entails an increased satiety and satiation within 7 days after its initiation; weight loss is pronounced over time [ 9 , 10 , 11 ]. A reduced irritability around eating was noted [ 11 ]. A 9-year-old female no longer secretly sought food or demanded food between meals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with recombinant human leptin (r-metHuLeptin; metreleptin) of patients with CLD entails an increased satiety and satiation within 7 days after its initiation; weight loss is pronounced over time [ 9 , 10 , 11 ]. A reduced irritability around eating was noted [ 11 ]. A 9-year-old female no longer secretly sought food or demanded food between meals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent report of a patient with leptin deficiency receiving supplementation, highlights key interactions between gut hormones. Treatment with leptin led to significant rises in meal-stimulated GLP-1, PYY and insulin levels, whereas ghrelin levels decreased [49]. This effect highlights the regulatory effect of leptin on ghrelin secretion and the interplay between leptin, GLP-1 and PYY.…”
Section: Gut Hormones In Obesity Pathophysiology: Cause or Consequence?mentioning
confidence: 78%
“…A previous study of children with severe, early-onset obesity similarly found a strong negative correlation between BMI values and LEP-SDS [33]. The authors hypothesize that this finding might be a sign of relative leptin deficiency, probably driven through the development of strong insulin resistance, and suggested that these children may benefit from a substitution with human recombinant leptin [33,34]. Genetic obesity is rare; therefore, identifying and diagnosing cases of genetic obesity is quite challenging for pediatricians.…”
Section: Discussionmentioning
confidence: 90%